Chemical Composition and In Vitro Antioxidant and Antimicrobial Activities of Marrubium vulgare L. - Ibrahim Mssillou; Abdelkrim Agour; Noureddine Hamamouch; Badiaa Lyoussi; Elhoussine Derwich (The Scientific World Journal)
In this study, the polyphenol content and the antioxidant and antimicrobial activities of hydroethanolic (MVE) and hydroacetonic (MVA) leaf extracts of Marrubium vulgare L. were examined. The results indicated that the total phenolic content was higher in MVA (112.09 ± 4.77 mg GAE/DW) compared to MVE extract (98.77 ± 1.68 mg GAE/DW). The total flavonoid content was also higher in MVA extract (21.08 ± 0.38 mg QE/g DW) compared to MVE (17.65 ± 0.73 mg QE/g DW). Analysis of the chemical composition revealed the presence of 13 compounds with a total of 96.14%, with the major compound being malic acid (22.57%). Both extracts possess a good total antioxidant activity. DPPH and FRAP assays indicated that the MVE extract possesses a better antioxidant activity, with IC50 = 52.04 µg/mL ± 0.2 and EC50 of 4.51 ± 0.5 mg/mL, compared to MVA extract (IC50 = 60.57 ± 0.6 µg/mL and EC50 of 6.43 ± 0.0411 mg/mL). Moreover, both extracts exhibited strong antimicrobial activity against certain nosocomial strains as indicted by the MIC values, which ranged between 0.93 mg/mL and 10 mg/mL. Taken together, these results reveal the importance of M. vulgare as a natural antioxidant with important antimicrobial activity.